2022
DOI: 10.3390/brainsci12091201
|View full text |Cite
|
Sign up to set email alerts
|

Functional Coupling between the Fronto-Parietal Network and Default Mode Network Is Associated with Balanced Time Perspective

Abstract: Balanced time perspective refers to the ability to flexibly switch between different temporal foci in an adaptive manner according to the current context. Functional connectivity within the default mode network (DMN) has been suggested to support balanced time perspective. The coupling between the DMN and fronto-parietal network (FPN) may drive many important expressions of internally directed cognition. However, it remains unclear whether balanced time perspective is supported by the interaction between the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In a task-induced fatigue study that measured the degree of being rested using a visual analogue scale, decreased frontoparietal network activity was detected ( Esposito et al, 2014 ). In a resting-state study of young adults, a negative correlation was found between connectivity in the dorsolateral prefrontal cortex (Brodmann areas 9 and 46) and wellbeing was found ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a task-induced fatigue study that measured the degree of being rested using a visual analogue scale, decreased frontoparietal network activity was detected ( Esposito et al, 2014 ). In a resting-state study of young adults, a negative correlation was found between connectivity in the dorsolateral prefrontal cortex (Brodmann areas 9 and 46) and wellbeing was found ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…DAN, an antagonist network of the DMN [35] , responds via directing bottom-up attention to salient environmental stimulation when the brain is engaged in attentionally demanding cognitive processes [36] . The FPN is a practical hub that in uences whole-brain conversation to meet multiple demand tasks, with areas of the lateral frontal cortex, dorsomedial frontal cortex, and parietal cortex involved [37,38] . These areas within the FPN are activated for the duration of duties requiring cognitive management or executive function [39] .…”
Section: Discussionmentioning
confidence: 99%